Digitalization and Cyberfeminism: Reinterpreting Islamic Criminal Law for Gender Equality and Women’s Rights - Imroatul Azizah; Lisa Aminatul Mukaromah; Khurul Anam; Sanuri Sanuri; Nafi' Mubarok (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
The rapid development of digital technology has transformed social interaction while simultaneously increasing women’s vulnerability to online gender-based violence, including revenge pornography, cyber harassment, and doxxing. Existing studies in cyberfeminism and digital legal scholarship demonstrate that digital spaces often reproduce patriarchal structures and discriminatory practices against women. Meanwhile, contemporary Islamic legal studies indicate that maqāṣid al-sharī‘ah possesses conceptual flexibility to respond to emerging socio-technological issues; however, these perspectives are rarely integrated systematically within the discourse of Islamic Criminal Law (fiqh al-jināyah). This study aims to reinterpret fiqh al-jināyah through the frameworks of maqāṣid al-sharī‘ah and cyberfeminism in order to construct a more inclusive and adaptive legal paradigm for protecting women’s rights in the digital era. Employing a normative juridical method, this research analyzes primary Islamic legal sources, classical fiqh literature, fatāwā, and Indonesian statutory regulations, including the Electronic Information and Transactions Law (UU ITE), the Personal Data Protection Law (UU PDP), and the Sexual Violence Crime Law (UU TPKS). The study also incorporates contemporary literature on cyberfeminism, digital violence, and gender justice. The findings reveal that the principles of maqāṣid al-sharī‘ah, particularly ḥifẓ al-‘irḍ (protection of dignity) and ḥifẓ al-nafs (protection of life), provide a strong normative foundation for categorizing digital gender-based violence as jarīmah ta‘zīr requiring adaptive sanctions. Furthermore, cyberfeminism contributes a transformative epistemological approach by repositioning women as active agents in legal interpretation and reform. This study ultimately contributes to the reconstruction of Islamic criminal jurisprudence that is gender-sensitive, contextually responsive, and aligned with the realities of contemporary digital society.